Recommendations to improve physical activity among teenagers- A qualitative study with ethnic minority and European teenagers - Choudhury Sopna; Hill Rebecca; Mistry Rupal; Crowley Annie; Brophy Sinead; Thomas Non E; Rapport Frances (BMC, 2011)
Abstract Background To understand the key challenges and explore recommendations from teenagers to promote physical activity with a focus on ethnic minority children. Methods Focus groups with teenagers aged 16-18 of Bangladeshi, Somali or Welsh descent attending a participating school in South Wales, UK. There were seventy four participants (18 Somali, 24 Bangladeshi and 32 Welsh children) divided into 12 focus groups. Results The boys were more positive about the benefits of exercise than the girls and felt there were not enough facilities or enough opportunity for unsupervised activity. The girls felt there was a lack of support to exercise from their family. All the children felt that attitudes to activity for teenagers needed to change, so that there was more family and community support for girls to be active and for boys to have freedom to do activities they wanted without formal supervision. It was felt that older children from all ethnic backgrounds should be involved more in delivering activities and schools needs to provide more frequent and a wider range of activities. Conclusions This study takes a child-focused approach to explore how interventions should be designed to promote physical activity in youth. Interventions need to improve access to facilities but also counteract attitudes that teenagers should be studying or working and not 'hanging about' playing with friends. Thus, the value of activity for teenagers needs to be promoted not just among the teenagers but with their teachers, parents and members of the community.